Health Tourism Through Panchakarma with Special Reference of Sharadiya Virechana - Shubham Golokkumar Biswas; Gandhali Upadhya; Devyani Dasar; Alok kumar Diwedi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Globalization is the process of international integration arising from interchange of the world’s views,products, ideas and other aspects of the culture. Ayurveda has holistic approach towards health and diseases,lifestyle, using medications, diet and their fewer side effect .Globalization helps to propagate Ayurvedaworldwide with the help of health tourism.India is emerging as a great destination for health tourism because it has several factors like excellentmedical treatment at low cost, easy accessibility, picturesque locations for excellent holidays etc. Healthtourism is not only beneficial for the foreigners but our country can also be benefitted financially. It willalso help to spread the importance of Ayurveda worldwide. The physician can extend a helping hand inglobalization of Ayurveda by being in their own motherland. Patients from industrialized nations seek healthtourism because of high quality treatment at low cost.Panchakarma is one of the specialty of Kayachikitsa presents unique approach of Ayurveda with shodhanaprocedures of the body. Panchakarma provides promotive, preventive, curative and rehabilative aspect.There has been phenomenal increase in the demand for Panchakarma. Sharad ritu is the time for Pittaprakopa. The pitta which was accumulated in Varsha ritu gets provoked by ushna guna during this season. Ifproper care is not taken during this time, it will cause Pittaja vikara. Virechana is the method of purification,conducted in Sharad ritu for preventing and controlling pitta prakopa as a part of Ritukalina shodhana.In this current paper, we would like to discuss different aspects of health tourism with special reference toSharadiya Virechana, which will contribute to propagate Ayurveda globally.